Euro, crisis and unemployment: youth patterns, youth policies? - Ghoshray, Atanu; Ordóñez, Javier; Sala, Hector (Bonn, 2016)
"This paper examines the occurrence of structural breaks in European unemployment associated with major events experienced by the European economies at an institutional level: the creation of the European and Monetary Union (EMU) in 1999, and the Euro/financial crisis in 2008-2009, which was followed by a general and intensive reform process in the years afterwards. Beyond the well documented asymmetries across countries, we uncover different responses of adult and youth unemployment rates. While adult unemployment is more prone to experience structural breaks, youth unemployment is more sensitive to business cycle oscillations. This has been especially so in the recent crisis and calls for fine tuning policy measures specifically targeted to youth unemployed in bad times. One important implication of our findings is that generic labour market reforms are not effective enough to solve the youth unemployment problem across Europe. We point to educational policies that raise average qualifications and help school-to-work transitions as suitable complementary cures."